Tracking the nature and trajectory of social support in Facebook mutual aid groups during the COVID-19 pandemic. (15th June 2022) - Ntontis, Evangelos; Fernandes-Jesus, Maria; Mao, Guanlan; Dines, Tom; Kane, Jazmin; Karakaya, Joshua; Perach, Rotem; Cocking, Chris; McTague, Michael; Schwarz, Anna; Semlyen, Joanna; Drury, John
Abstract: At the onset of the COVID-19 pandemic, thousands of mutual aid groups were established on social media and operated as platforms through which people could offer or request social support. Considering the importance of Facebook mutual aid groups during the early stages of the COVID-19 pandemic in the United Kingdom but also the lack of empirical research regarding the trajectories and types of social support rendered available through the groups, our aims in this paper are threefold; first, to examine the trajectory of social support-related activity during the period between March–December 2020; second, to compare offers and requests of support during the peaks of the first and second waves; third to provide a rich analysis of the types of social support that were offered or requested through the online mutual aid groups. Quantitative findings suggest that online social support activity declined soon after the peak of the first pandemic wave and, at least in Facebook mutual aid groups, did not reach the levels observed during the first wave. Also, the number of offers of support during the first wave was higher compared to offers during the second wave, and similar was the case for requests for support. Additionally, offers for support were higher compared to requests for support during both the first and second waves. Finally, qualitative analysis showed that people used the Facebook mutual aid groups to offer and request various types of practical, emotional, and informational support. Limitations as well as implications of our study are considered. Highlights: During COVID-19, support was offered or requested through online mutual aid groups. People offered or requested practical, emotional, and informational support. Support activity in UK Facebook groups declined after the first pandemic wave. Both offers and requests for support were higher in Wave 1 compared to Wave 2. Offers of support were higher compared to requests during both Wave 1 and Wave 2.